Double qualifications and gender: The case of Germany - Bellmann, Lutz; Prümer , Stephanie (Bulletin of Geography. Socio-economic Series, 2023)
After obtaining the German upper secondary school-leaving certificate (Abitur), school-leavers are free in their choice of career path. Obtaining a double qualification by first completing an apprenticeship and then graduate from university is thereby popular. Using the BIBB/BAuA Employment Survey of the Working Population on Qualification and Working Conditions 2018, this paper analyses the individual effects of these double qualifications by exploiting the rich information on education in the data. In relation to earlier studies, we find that the proportion of men gaining a double qualification decreased by 8 percentage points but is almost constant for women. Furthermore, we detect a significantly negative effect of double qualification on wages for women, but no significant effect on wages for men. We presume that these changes may be related to the rising inequality due to the rising number of academics and the increase of earnings inequality.